Eksperimen Visual Arsitektur Vernakular: Refleksi Artistik Melalui Tiga Teknik Sketsa Rumah Panggung di Desa Wana - Miky Endro Santoso; Tessa Eka Darmayanti (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This study examines the visual characteristics of vernacular stilt-house architecture in Wana Village, East Lampung, through three sketching techniques: drawing pen, drawing pen with watercolor, and drawing pen with colored pencils. This traditional house was chosen because it holds significant architectural and cultural value as a representation of the local identity of the Lampung community, reflecting adaptation to the tropical environment, the use of natural materials, and traditional construction systems passed down through generations. Amid the ongoing modernization that threatens to alter and diminish local architectural traditions, this study is crucial as an effort to document and preserve visual knowledge that represents the interrelation between architecture, culture, and environment. The purpose of this research is to explore how different visual media influence architectural representation in terms of detail, texture, depth, and visual nuance. The study employs a qualitative exploratory, experimental approach within the framework of practice-based research. Data were obtained from photographic documentation of vernacular stilt houses, which served as visual references during the reflective sketching process. The results show that each medium produces distinct aesthetic and cultural interpretations: drawing pen emphasizes structural clarity; the combination of drawing pen and watercolor presents harmony between architecture and the environment; while drawing pen with colored pencils conveys more personal and emotional expression. Through artistic reflection and iterative evaluation, this creative practice provides new insights into the relationship between visual action and cultural meaning. The study concludes that reflective sketching can serve as a visual research method that integrates artistic knowledge, aesthetic experience, and the identity of vernacular architecture.